Vinyl acetate catalyst and preparation method thereof, vinyl acetate catalytic composition and method for preparing vinyl acetate
By using MOFs support to support divalent zinc compound vinyl acetate catalyst and compounding with traditional catalysts, the problems of poor selectivity of existing catalysts and many by-products are solved, and the efficient preparation of vinyl acetate is achieved, which improves the application ability of the product in the field of high value-added fields.
Patent Information
- Application Number
- CN202311472873.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-05-09
AI Technical Summary
The existing acetylene vinyl acetate catalyst has poor selectivity, many by-products, and high content of benzene impurities, making it difficult for products to be widely used in high value-added fields, and the profitability of enterprises is limited.
Metal organic frame materials (MOFs) are used as support to support divalent zinc compounds, vinyl acetate catalysts are prepared and combined with traditional activated carbon/zinc acetate catalysts to improve the activity and selectivity of the catalyst.
It significantly reduces the content of the key by-product benzene in the product, improves the activity and selectivity of the catalyst, enhances the application potential of vinyl acetate in the field of high value-added, and improves the profitability of the enterprise.
Smart Images

Figure BDA0004535762680000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a vinyl acetate catalyst and a preparation method thereof, a vinyl acetate catalyst composition and a method for preparing vinyl acetate. Background Art
[0002] Vinyl acetate, referred to as vinyl acetate (VAM), is an important organic chemical raw material, mainly used in the production of polyvinyl alcohol (PVOH), polyvinyl acetate (PVAc), vinyl acetate-ethylene copolymer emulsion (VAE) or copolymer resin (EVA) and other derivatives, and has a wide range of applications.
[0003] At present, the global vinyl acetate production capacity is about 8.7 million tons / year, and its main production process routes include ethylene method and acetylene method. Among them, the acetylene process is divided into natural gas acetylene process and calcium carbide acetylene process. my country's vinyl acetate production capacity has reached 3 million tons / year, mainly based on the acetylene production process. This process route has certain advantages over the calcium carbide acetylene process in terms of product quality and green environmental protection.
[0004] The natural gas acetylene production process adopts a fixed bed reactor process and uses zinc acetate / activated carbon as a catalyst. The catalyst has the advantages of abundant raw material sources, simple preparation process, and low production cost. However, the traditional zinc acetate / activated carbon catalyst has the problems of insufficient selectivity and a large number of by-products, especially the presence of by-product benzene in the product vinyl acetate. Since benzene and vinyl acetate have similar boiling points and kinetic molecular sizes, it is difficult to effectively remove them through distillation technology. The presence of benzene will make it difficult for acetylene-based vinyl acetate to be widely used in downstream high-value-added fields such as photovoltaic films, food packaging films, cigarette glue, and chewing gum bases, resulting in a relative surplus of acetylene-based vinyl acetate products and pressure on corporate profitability. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor selectivity, large number of reaction by-products and high benzene impurity content of acetylene-based vinyl acetate catalysts in the prior art, and to provide a vinyl acetate catalyst and a preparation method thereof, a vinyl acetate catalytic composition and a method for preparing vinyl acetate. The catalyst has high catalytic activity and few by-products.
[0006] In order to achieve the above object, the first aspect of the present invention provides a vinyl acetate catalyst, which includes a MOFs material and a divalent zinc compound supported on the MOFs material.
[0007] Preferably, the MOFs material is ZIF-8.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned vinyl acetate catalyst, comprising:
[0009] The MOFs material is contacted with a solution containing a divalent zinc compound and then dried.
[0010] The third aspect of the present invention provides a vinyl acetate catalytic composition, the composition comprising a catalyst A and a catalyst B, wherein the catalyst A is the vinyl acetate catalyst described in the first aspect; the catalyst B comprises a carbon carrier and a divalent zinc compound supported on the carbon carrier;
[0011] Preferably, the mass ratio of the catalyst A to the catalyst B is 1:(1-10).
[0012] A fourth aspect of the present invention provides a method for preparing vinyl acetate, comprising: contacting acetic acid and acetylene with a catalyst under vinyl acetate synthesis conditions to obtain vinyl acetate;
[0013] Wherein, the catalyst is the vinyl acetate catalyst described in the first aspect or the vinyl acetate catalyst composition described in the third aspect.
[0014] In the catalyst of the prior art, the carrier is usually activated carbon, and the active component is zinc acetate, the catalyst selectivity is low, and there are many by-products. The vinyl acetate catalyst provided by the present invention uses metal organic framework materials (MOFs) as a carrier, loads a divalent zinc compound, has a high catalytic activity, and can reduce the content of key by-product benzene in the product. Further compounding the catalyst with the existing activated carbon / zinc acetate catalyst can further improve the activity and selectivity of the catalyst. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] A first aspect of the present invention provides a vinyl acetate catalyst, which includes an MOFs material and a divalent zinc compound supported on the MOFs material.
[0017] In the catalysts of the prior art, the carrier is usually activated carbon, and the active component is zinc acetate. The inventors of the present invention have found in experiments that the use of the above-mentioned traditional vinyl acetate catalyst has the problem of a large number of by-products, especially the presence of by-product benzene in the product vinyl acetate, which will make it difficult for acetylene-based vinyl acetate to be widely used in high value-added fields such as photovoltaic films, food packaging films, cigarette glue, and chewing gum bases. In order to solve the above problems, the inventors of the present invention creatively proposed to use MOFs materials as carriers of vinyl acetate catalysts. After loading divalent zinc compounds, the content of key by-product benzene in the product can be reduced and the catalytic activity is higher. The reason may be that the MOFs material has a special pore structure and metal ion characteristics, which inhibits the occurrence of side reactions of acetylene synthesizing benzene.
[0018] In the present invention, the "MOFs material" has the conventional definition in the art, and refers to a metal organic framework compound (Metal organic Framework), which is a type of crystalline porous material with a periodic network structure formed by the self-assembly of an inorganic metal center (metal ion or metal cluster) and a bridging organic ligand. The present invention has a wide range of selection for the MOFs material. Preferably, the MOFs material is a zeolite imidazolate metal-organic framework material (ZIFs), preferably at least one of ZIF-8, ZIF-67, ZIF-62, and ZIF-68, more preferably ZIF-8 and / or ZIF-67, and most preferably ZIF-8. The use of the above-mentioned preferred MOFs material is conducive to further reducing the content of key impurity benzene in vinyl acetate products.
[0019] According to some preferred embodiments of the present invention, the MOFs material comprises metal ions and organic ligands, and the metal ions in the MOFs material are selected from at least one of transition metal ions, preferably Zn 2+ 、Co 2+ , Cu 2+ and Fe 2+ At least one of .
[0020] Preferably, the organic ligand in the MOFs material is selected from at least one of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-nitroimidazole and benzimidazole.
[0021] According to some preferred embodiments of the present invention, the molar ratio of metal ions to organic ligands in the MOFs material is 1:(0.1-10), preferably 1:(1-7).
[0022] According to the present invention, preferably, the specific surface area of the MOFs material is 600-1000m 2 / g, preferably 700-900m 2 / g.
[0023] Preferably, the pore volume of the MOFs material is 0.4-0.8 mL / g, preferably 0.5-0.7 mL / g.
[0024] In the present invention, the specific surface area and pore volume of the MOFs material are obtained by static volumetric testing.
[0025] According to some preferred embodiments of the present invention, in the catalyst, the content of the divalent zinc compound in terms of element is 40-100 g / L, preferably 50-70 g / L. Controlling the content of the divalent zinc compound within the above preferred range is conducive to maintaining a high catalytic activity and a long service life of the catalyst.
[0026] In the present invention, a Thermo iCAP 6300 inductively coupled plasma spectrometer (ICP-AES) is used to quantitatively analyze the elements in the catalyst.
[0027] According to the present invention, preferably, the divalent zinc compound is zinc acetate.
[0028] The second aspect of the present invention provides a method for preparing the above-mentioned vinyl acetate catalyst, comprising:
[0029] The MOFs material is contacted with a solution containing a divalent zinc compound and then dried.
[0030] According to the present invention, preferably, the amount of the solution containing the divalent zinc compound and the MOFs material is such that the content of the divalent zinc compound in the prepared catalyst, calculated as the element, is 40-100 g / L, preferably 50-70 g / L.
[0031] Preferably, the divalent zinc compound is zinc acetate, and the solvent in the solution containing the divalent zinc compound may be water.
[0032] The present invention has no particular limitation on the specific operation and conditions of the contact in step (2), and can be carried out in a conventional manner in the art, as long as the divalent zinc compound can be loaded on the MOFs material, for example, the MOFs material can be impregnated with a solution containing a divalent zinc compound. Preferably, the concentration of the solution containing the divalent zinc compound is 10-200 g / L, preferably 50-150 g / L, in terms of zinc element.
[0033] The present invention has no special requirements for the contact conditions. In order to further improve the dispersibility of the divalent zinc compound and the binding force between the carrier and the divalent zinc compound, preferably, the contact temperature is 40-120°C and the time is 1-12h; more preferably, the contact temperature is 60-100°C and the time is 4-8h.
[0034] Preferably, the drying temperature is 40-140° C., and the drying time is 1-24 h; further preferably, the drying temperature is 60-100° C., and the drying time is 4-10 h.
[0035] In the present invention, the preparation method does not include a calcination process.
[0036] The MOFs material has the same definition as above and will not be described again. The source of the MOFs material is not particularly limited in the present invention and can be purchased from a commercial source or prepared by any method known in the art.
[0037] According to some preferred embodiments of the present invention, the method for preparing the MOFs material comprises:
[0038] Under stirring conditions, the organic ligand, transition metal salt and solvent are mixed, aged, and then solid-liquid separated, washed and dried.
[0039] According to the present invention, preferably, the molar ratio of the transition metal salt to the organic ligand calculated as metal element is 1:(1-7), preferably 1:(2-6).
[0040] The selection of the organic ligand is the same as the definition range in the above text. Preferably, the organic ligand is selected from at least one of imidazole, 2-methylimidazole, 2-ethylimidazole and 2-nitroimidazole.
[0041] The present invention has a wide range of selection for the metal element in the transition metal salt, and any transition metal that helps to form a metal organic framework can be applied to the present invention. Preferably, the metal element in the transition metal salt is selected from Zn 2+ 、Co 2 + , Cu 2+ , Fe 2 The use of the preferred metal composition is beneficial to further inhibit the formation of benzene as a by-product in the synthesis of vinyl acetate.
[0042] The present invention has no particular requirements for the type of the transition metal salt, and a soluble salt of a conventional transition metal in the art can be used, for example, at least one of a nitrate, a hydrochloride, and an acetate. The transition metal salt may also contain crystal water, which is well known to those skilled in the art and will not be described in detail herein.
[0043] The present invention has a wide range of choices for the solvent. Preferably, the solvent is a low-carbon alcohol, such as methanol and / or ethanol. The present invention also has no particular limitation on the amount of the solvent, as long as it can fully dissolve the reactants, and those skilled in the art can select it according to actual needs.
[0044] According to the present invention, the mixing in step (1) is carried out under stirring conditions. The present invention has no particular requirements for the speed of the stirring, as long as the reactants are fully mixed. Preferably, the stirring time is 10-600 min.
[0045] According to some preferred embodiments of the present invention, the conditions of the aging treatment include: a temperature of 20-60°C, preferably 20-40°C; and a time of 12-48h, preferably 16-36h.
[0046] According to the present invention, the preparation method further comprises: subjecting the product after the aging treatment to solid-liquid separation, washing and drying. The present invention has no particular limitation on the specific operation mode of the solid-liquid separation, and it can be carried out in a conventional manner in the art, for example, it can be carried out by filtering or centrifugation. The present invention has no particular requirements for the washing method, as long as it is conducive to removing unreacted reactants from the product. The present invention has no particular requirements for the number of washings, and those skilled in the art can select according to actual needs. The washing detergent can be, for example, an alcohol, preferably at least one of methanol, ethanol, and isopropanol.
[0047] According to some preferred embodiments of the present invention, the drying temperature is 60-100° C., preferably 70-90° C.; the drying time is 6-24 h, preferably 9-18 h.
[0048] The third aspect of the present invention provides a vinyl acetate catalytic composition, which comprises a catalyst A and a catalyst B, wherein the catalyst A is the vinyl acetate catalyst described in the first aspect; and the catalyst B comprises a carbon carrier and a divalent zinc compound loaded on the carbon carrier.
[0049] According to the present invention, the MOFs material / zinc catalyst provided by the present invention is further compounded with the existing activated carbon / zinc catalyst, which can further improve the activity and selectivity of the catalyst and ensure that the content of the key byproduct benzene is reduced to below 1 ppm.
[0050] According to some preferred embodiments of the present invention, the mass ratio of the catalyst A to the catalyst B is 1:(0.1-20), preferably 1:(1-10). The above preferred embodiments are advantageous for achieving the purpose of reducing the key impurity benzene in the product vinyl acetate, while reducing the catalyst cost.
[0051] The present invention has a wide range of selection for the specific composition of the catalyst B, and any conventional carbon-based catalyst that can be used for vinyl acetate synthesis in the art can be applied to the present invention.
[0052] According to some preferred embodiments of the present invention, the carbon carrier is activated carbon. Preferably, the specific surface area of the carbon carrier is 1000-1300m 2 / g, and the pore volume is 0.4-0.8mL / g. The above preferred implementation is beneficial for the catalyst to maintain high activity and selectivity.
[0053] According to some preferred embodiments of the present invention, in the catalyst B, the content of the divalent zinc compound calculated as the element is 40-80 g / L, preferably 50-70 g / L.
[0054] According to the present invention, preferably, the catalyst B further comprises an auxiliary component supported on the carbon carrier, and the auxiliary component is selected from at least one of bismuth, barium and cadmium, preferably bismuth. The auxiliary component and the divalent zinc compound act synergistically, and are further compounded with the catalyst A, which is conducive to further improving the catalyst activity and reducing the key impurity benzene content.
[0055] According to some preferred embodiments of the present invention, in the catalyst B, the content of the auxiliary component calculated as an element is 0-1 g / L, preferably 0.1-0.5 g / L.
[0056] The present invention has no particular limitation on the source of the catalyst B, which can be purchased from commercial sources or prepared using methods known in the art.
[0057] According to some preferred embodiments of the present invention, the preparation method of the catalyst B comprises: impregnating a carbon support with an impregnation solution containing a divalent zinc compound, and then drying the carbon support. The impregnation solution optionally comprises a soluble compound of an auxiliary component.
[0058] The amount of the impregnation solution used is based on the amount of the divalent zinc compound and / or the auxiliary component in the catalyst B to be loaded.
[0059] According to some preferred embodiments of the present invention, the immersion conditions include: a temperature of 60-120° C. and a time of 2-24 h.
[0060] Preferably, the drying conditions include: drying temperature of 60-120° C. and drying time of 3-24 h.
[0061] In the present invention, the method for preparing the vinyl acetate catalyst composition comprises: mixing catalyst A and catalyst B. The present invention has no special requirements for the mixing method, as long as catalyst A and catalyst B are mixed uniformly.
[0062] A fourth aspect of the present invention provides a method for preparing vinyl acetate, comprising: contacting acetic acid and acetylene with a catalyst under vinyl acetate synthesis conditions to obtain vinyl acetate;
[0063] Wherein, the catalyst is the vinyl acetate catalyst described in the first aspect or the vinyl acetate catalyst composition described in the third aspect.
[0064] According to the present invention, the vinyl acetate catalyst described in the first aspect can be used alone as a vinyl acetate catalyst, or can be used as a catalyst composition with a conventional carbon-based vinyl acetate catalyst. Preferably, the catalyst is the vinyl acetate catalyst composition described in the third aspect. The use of the above preferred embodiment is conducive to further improving the activity and selectivity of the catalyst, with a high space-time yield and the content of the key byproduct benzene in the product can be reduced to less than 1ppm.
[0065] The present invention has a wide range of selection conditions for the synthesis of vinyl acetate. Preferably, the reaction temperature for the synthesis of vinyl acetate is 160-220°C, preferably 165-215°C, for example, it can be 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C and other typical but non-limiting temperature values or ranges therebetween.
[0066] Preferably, the reaction pressure of the vinyl acetate synthesis is 0.1-0.5 atm, preferably 0.15-0.45 atm, for example, 0.15 atm, 0.2 atm, 0.25 atm, 0.3 atm, 0.35 atm, 0.4 atm, 0.45 atm, etc., or a range therebetween. In the present invention, unless otherwise specified, the pressure refers to the gauge pressure.
[0067] Preferably, the raw material volume space velocity for vinyl acetate synthesis is 250-350h -1 , preferably 260-340h -1 、260h -1 、270h -1 、280h -1 、290h -1 、300h -1 、310h -1 、320h -1 、330h -1 、340h -1 isovolumetric airspeed value or a range between them.
[0068] Preferably, the molar ratio of acetylene to acetic acid is 5-12, preferably 6-11, for example but not limited to 6, 7, 8, 9, 10, 11 or the range therebetween.
[0069] The present invention will be described in detail below through examples.
[0070] In the present invention, a Thermo iCAP 6300 inductively coupled plasma spectrometer (ICP-AES) is used to quantitatively analyze the elements in the catalyst.
[0071] In the present invention, in the embodiments and comparative examples, the specific surface area of the carrier is measured by using a Micromeritics ASAP 2460 specific surface area and porosity analyzer. Accurately weigh a certain amount of sample and pre-treat it at 60°C under vacuum to 1×10 -5 After the adsorption of N 2 The adsorbate was adsorbed and the adsorption and desorption were measured at liquid nitrogen temperature. BET Calculated by BET equation.
[0072] The following preparation example is used to illustrate the preparation of Catalyst B.
[0073] Preparation Example 1
[0074] 0.1 L of zinc acetate aqueous solution containing bismuth subcarbonate (zinc concentration: 60 g / L) was prepared and mixed with 0.1 L of activated carbon carrier (purchased from Shanghai Xinhui Activated Carbon Co., Ltd., with a specific surface area of 1200 m 2 / g, pore volume of 0.6mL / g) were mixed, impregnated at 80°C for 2h, and dried at 110°C for 6h to obtain catalyst B1.
[0075] According to ICP-AES measurement, the Zn content in the catalyst is 60 g / L, and the Bi content is 0.25 g / L.
[0076] Preparation Example 2
[0077] Prepare 0.1L of zinc acetate aqueous solution (zinc concentration: 60g / L) and mix it with 0.1L of activated carbon carrier (purchased from Shanghai Xinhui Activated Carbon Co., Ltd., with a specific surface area of 1200m 2 / g, pore volume of 0.6mL / g), immersed at 80℃ for 2h, and dried at 110℃ for 6h to obtain catalyst B2.
[0078] The Zn content in the catalyst was determined by ICP-AES to be 60 g / L.
[0079] The following example illustrates the preparation of Catalyst A.
[0080] Example 1-1
[0081] (1) Dissolve zinc nitrate hexahydrate and 2-methylimidazole in methanol to prepare zinc nitrate hexahydrate methanol solution and 2-methylimidazole methanol solution. 2+The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole was 1:4, and the methanol solution of zinc nitrate hexahydrate was added to the methanol solution of 2-methylimidazole, stirred for 10 minutes, aged at 30°C for 24 hours, and finally the white precipitate was centrifuged, washed with methanol several times, and dried at 80°C for 12 hours to obtain the carrier ZIF-8.
[0082] The specific surface area of the carrier ZIF-8 was determined by a surface area and porosity analyzer to be 880 m 2 / g, and the pore volume is 0.6mL / g.
[0083] (2) Prepare 0.1 L of zinc acetate aqueous solution (zinc concentration: 60 g / L), mix it with 0.1 L of ZIF-8 carrier, immerse it at 80° C. for 2 h, and dry it at 110° C. for 6 h to obtain catalyst A1.
[0084] The Zn content in the catalyst was determined by ICP-AES to be 60 g / L.
[0085] Example 1-2
[0086] (1) Dissolve zinc nitrate hexahydrate and imidazole in methanol to prepare zinc nitrate hexahydrate methanol solution and imidazole methanol solution. 2+ The molar ratio of zinc nitrate hexahydrate to imidazole was 1:2, and the methanol solution of zinc nitrate hexahydrate was added to the methanol solution of imidazole, stirred for 20 minutes, aged at 30°C for 24 hours, and finally the white precipitate was centrifuged, washed several times with methanol, and dried at 80°C for 12 hours to obtain the carrier ZIF-8.
[0087] The specific surface area of the carrier ZIF-8 was determined by a surface area and porosity analyzer to be 845 m 2 / g, and the pore volume is 0.55mL / g.
[0088] (2) 0.1 L of zinc acetate aqueous solution (zinc concentration: 50 g / L) was prepared, mixed with 0.1 L of ZIF-8 carrier, immersed at 80° C. for 2 h, and dried at 110° C. for 6 h to obtain catalyst A2. The Zn content in the catalyst was 50 g / L as determined by ICP-AES.
[0089] Examples 1-3
[0090] (1) Cobalt nitrate hexahydrate and 2-methylimidazole were dissolved in methanol to prepare cobalt nitrate hexahydrate methanol solution and 2-methylimidazole methanol solution. 2+ The molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole was 1:4, and the methanol solution of cobalt nitrate hexahydrate was added to the methanol solution of 2-methylimidazole, stirred for 20 minutes, aged at 30°C for 24 hours, and finally the white precipitate was centrifuged, washed several times with methanol, and dried at 80°C for 12 hours to obtain the carrier ZIF-67.
[0091] The specific surface area of the carrier ZIF-67 was determined by a surface area and porosity analyzer to be 858 m 2 / g, and the pore volume is 0.57mL / g.
[0092] (2) Prepare 0.1 L of zinc acetate aqueous solution (zinc concentration: 70 g / L), mix it with 0.1 L of ZIF-67 carrier, immerse it at 80° C. for 2 h, and dry it at 110° C. for 6 h to obtain catalyst A3.
[0093] The Zn content in the catalyst was determined by ICP-AES to be 70 g / L.
[0094] Examples 1-4
[0095] (1) Dissolve zinc nitrate hexahydrate in methanol to prepare a zinc nitrate hexahydrate methanol solution, dissolve a mixture of imidazole and benzimidazole (molar ratio 7:1) in a methanol solution to prepare a ligand solution, and 2+ The total molar ratio of imidazole to benzimidazole was 1:4, and the hexahydrated zinc nitrate methanol solution was added to the ligand solution, stirred for 20 minutes, aged at 30°C for 24 hours, and finally the white precipitate was centrifuged, washed several times with methanol, and dried at 80°C for 12 hours to obtain the carrier ZIF-62.
[0096] The specific surface area of the carrier ZIF-62 was 525 m 2 / g, and the pore volume is 0.47mL / g.
[0097] (2) Prepare 0.1 L of zinc acetate aqueous solution (zinc concentration: 60 g / L), mix it with 0.1 L of ZIF-62 carrier, immerse it at 80° C. for 2 h, and dry it at 110° C. for 6 h to obtain catalyst A4.
[0098] The Zn content in the catalyst was determined by ICP-AES to be 60 g / L.
[0099] The following examples are used to illustrate the preparation of the vinyl acetate catalyst composition of the present invention.
[0100] Example 2-1
[0101] Catalyst A1 and catalyst B1 were mixed in a mass ratio of 1:4, and the obtained catalyst composition was recorded as S1.
[0102] Example 2-2
[0103] Catalyst A2 and catalyst B1 were mixed in a mass ratio of 1:1, and the obtained catalyst composition was recorded as S2.
[0104] Example 2-3
[0105] Catalyst A3 and catalyst B1 were mixed at a mass ratio of 1:10, and the obtained catalyst composition was recorded as S3.
[0106] Embodiment 2-4
[0107] Catalyst A4 and catalyst B1 were mixed in a mass ratio of 1:4, and the obtained catalyst composition was recorded as S4.
[0108] Embodiment 2-5
[0109] The method of Example 2-1 was followed, except that the mass ratio of catalyst A1 to catalyst B1 was 1:0.5. The obtained catalyst composition was recorded as S5.
[0110] Embodiment 2-6
[0111] The method of Example 2-1 was followed, except that an equal mass of catalyst B2 was used to replace catalyst B1. The resulting catalyst composition was recorded as S6.
[0112] Application Examples
[0113] In a fixed bed reactor, vinyl acetate synthesis reaction was carried out with a catalyst loading of 40 mL. The catalyst composition and reaction conditions are shown in Table 1. The reaction products were collected every 1 h. The vinyl acetate content in the products was analyzed by gas chromatography. The benzene content in the products was analyzed by gas chromatography-mass spectrometry. The average space-time yield and selectivity of the reaction for 100 h were calculated.
[0114] In Table 1,
[0115] Space-time yield refers to the average space-time yield of the reaction for 100 hours, in g·(L·h) -1 .
[0116] Selectivity (%) = molar amount of acetic acid consumed to produce vinyl acetate / total molar amount of acetic acid consumed × 100%, in %.
[0117] Table 1
[0118]
[0119] From the results in Table 1, it can be seen that the vinyl acetate catalyst prepared in the embodiment of the present invention uses metal organic framework materials (MOFs) as a carrier, loads a divalent zinc compound, has a high catalytic activity, and can reduce the content of key byproduct benzene in the product. Further compounding the catalyst with an existing activated carbon / zinc acetate catalyst can further improve the activity and selectivity of the catalyst.
[0120] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A vinyl acetate catalyst, characterized in that: The catalyst comprises an MOFs material and a divalent zinc compound supported on the MOFs material.
2. The catalyst according to claim 1, wherein The MOFs material is a zeolite imidazolate metal-organic framework material, preferably at least one of ZIF-8, ZIF-67, ZIF-62 and ZIF-68, and more preferably ZIF-8 and / or ZIF-67; Preferably, the MOFs material comprises metal ions and organic ligands, wherein the metal ions are selected from at least one of transition metal ions, preferably Zn 2+ 、Co 2+ , Cu 2+ and Fe 2+ At least one of, more preferably Zn 2+ and / or Co 2+ ; Preferably, the organic ligand is selected from at least one of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-nitroimidazole and benzimidazole; Preferably, the molar ratio of metal ions to organic ligands in the MOFs material is 1:(0.1-10), preferably 1:(1-7).
3. The catalyst according to claim 1 or 2, wherein the specific surface area of the MOFs material is 600-1000m 2 / g, preferably 700-900m 2 / g; Preferably, the pore volume of the MOFs material is 0.4-0.8 mL / g, preferably 0.5-0.7 mL / g.
4. The catalyst according to any one of claims 1 to 3, wherein In the catalyst, the content of the divalent zinc compound in terms of element is 40-100 g / L, preferably 50-70 g / L; Preferably, the divalent zinc compound is zinc acetate.
5. The method for preparing the vinyl acetate catalyst according to any one of claims 1 to 4, comprising: The MOFs material is contacted with a solution containing a divalent zinc compound and then dried.
6. The preparation method according to claim 5, wherein: The amount of the solution containing the divalent zinc compound and the MOFs material is such that the content of the divalent zinc compound in the prepared catalyst is 40-100 g / L, preferably 50-70 g / L, calculated as the element; Preferably, the divalent zinc compound is zinc acetate; Preferably, the concentration of the solution containing the divalent zinc compound is 10-200 g / L in terms of zinc element; Preferably, the contacting temperature is 40-120°C and the contacting time is 1-12h; Preferably, the drying temperature is 40-140° C. and the drying time is 1-24 h.
7. The preparation method according to claim 5 or 6, wherein: The preparation method of the MOFs material comprises: mixing an organic ligand, a transition metal salt and a solvent under stirring conditions, performing an aging treatment, and then performing solid-liquid separation, washing and drying; Preferably, the molar ratio of the transition metal salt to the organic ligand calculated as the metal element is 1:(1-7); Preferably, the aging treatment conditions include: temperature of 20-60°C and time of 12-48h; Preferably, the drying temperature is 60-100° C. and the drying time is 6-24 hours.
8. A vinyl acetate catalyst composition, characterized in that: The composition comprises a catalyst A and a catalyst B, wherein the catalyst A is the vinyl acetate catalyst according to any one of claims 1 to 4; the catalyst B comprises a carbon carrier and a divalent zinc compound supported on the carbon carrier; Preferably, the mass ratio of the catalyst A to the catalyst B is 1:(0.1-20), preferably 1:(1-10).
9. The composition according to claim 8, wherein The carbon carrier is activated carbon. Preferably, the specific surface area of the carbon carrier is 1000-1300m 2 / g, pore volume is 0.4-0.8mL / g; Preferably, the catalyst B further comprises an auxiliary component supported on the carbon carrier, and the auxiliary component is selected from at least one of bismuth, barium and cadmium; Preferably, in the catalyst B, the content of the divalent zinc compound calculated as an element is 40-80 g / L, preferably 50-70 g / L; the content of the auxiliary component calculated as an element is 0-1 g / L, preferably 0.1-0.5 g / L.
10. A method for preparing vinyl acetate, comprising: Under vinyl acetate synthesis conditions, acetic acid and acetylene are contacted with a catalyst to obtain vinyl acetate; Wherein, the catalyst is the vinyl acetate catalyst according to any one of claims 1 to 4 or the vinyl acetate catalytic composition according to claim 8 or 9; Preferably, the vinyl acetate synthesis conditions include: reaction temperature of 160-220°C, reaction pressure of 0.1-0.5 atm, raw material volume space velocity of 250-350 h -1 , the molar ratio of acetylene to acetic acid is 5-12.